On the relation between the categories «social security» and «social welfare» of the Civil Aviation employees - Шапенко, Людмила Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author examines essence and features of the categories «social security» and «social welfare» on the basis of analysis of the different scientific approaches. These categories are separated and determined as a result of the author’s research in relation to the Civil Aviation employees.